Protoscolicidal effects of curcumin nanoemulsion against protoscoleces of Echinococcus granulosus - Aref Teimouri; Sanaz Jafarpour Azami; Saeedeh Hashemi Hafshejani; Mohammad Ghanimatdan; Mohammad Saleh Bahreini; Rasoul Alimi; Seyed Mahmoud Sadjjadi (BMC, 2023)
Abstract Background The aim of the present study was to assess in vitro protoscolicidal effects of curcumin nanoemulsion (CUR-NE) against protoscoleces of cystic echinococcosis (CE)/hydatid cysts. Methods The CUR-NE was prepared via spontaneous emulsification of soybean as the oil phase, a mixture of Tween 80 and Tween 85 as the surfactant, ethanol as the co-surfactant and distilled water. Various concentrations of CUR-NE (156, 312, 625 and 1250 µg/ml) were exposed to collected protoscoleces of infected sheep liver hydatid cysts for 10, 20, 30, 60 and 120 min. Viability of the protoscoleces were assessed using eosin exclusion test. Morphological changes of the protoscoleces were observed using differential interference contrast (DIC) microscopy. Results The mean particle size and zeta potential of CUR-NE included 60.4 ± 14.8 nm and − 16.1 ± 1.1 mV, respectively. Results showed that the viability of the protoscoleces decreased significantly with increases in CUR-NE concentrations (p < 0.001). The mortality rates of protoscoleces with exposure to concentrations of 1250 and 625 µg/ml of CUR-NE for 60 min were 94 and 73.33%, respectively. Mortality of the protoscoleces was 100% after 120 min of exposure to 1250 and 625 µg/ml concentrations of CUR-NE. Using NIC microscopy, extensively altered tegumental surface protoscoleces was observed after protoscoleces exposure to CUR-NE. Conclusion The findings of the present study revealed the in vitro protoscolicidal potential of CUR-NE. Therefore, CUR-NEs are addressed as novel protoscolicidal agents, which can be used as an alternative natural medicine to kill the protoscoleces, owing to their low toxicity and significant inhibition potency. However, further studies are necessary to investigate pharmacologic and pharmacokinetics of CUR-NEs.